Effect of carbon fiber reinforced polymer (CFRP) laminates on behaviour of flexural strength of steel beams with and without end anchorage plates. (2022) - AL-Ridha, Ahmed S.D.; Mahmoud, Kamal Sh.; Atshan, Ali F.
Abstract: Three steel beams were made-up and tested to study the effect of CFRP (Carbon Fiber Reinforced Polymer) laminates with and without end anchorage plates on the behavior of flexural strength of steel beams. Tested steel specimens are equal in clear span length, gross sectional area, and strengthened by intermediate stiffeners. Three types of specimens were made, the first specimen was considered as a reference one, while the other two were reinforced by CFRP laminates with and without end anchorage plates respectively. From the experimental outcomes, it was found that, the load deflection curve and load strain responses for specimens strengthened by CFRP strips became stiffer in comparison with the reference beam. On the other hand, it was found that, the deflection values for strengthened beams by CFRP without and with end anchorage plates were decreased to 58.33% and 79.95%, while, the strain values were decreased to 63% and 85.55% respectively, in comparison with the reference beam at yielding stage at load (Py = 20 kN) while, at failure stage at load (Pu = 45 kN) for reference beam, the deflection values for strengthened beams by CFRP without and with end anchorage plates were decreased to 81.19% and 88.13%, while, the strain values were decreased to 88.6% and 97.14% respectively, in comparison with the reference beam. Also, the percentages of increasing in yielding -load for strengthened beams by CFRP without and with end anchorage plates were increased to 100 % to 225 %, while, the percentages of increasing in ultimate-load for strengthened beams by CFRP without and with end anchorage plates were increased to 38.88 % to 111.11 %, respectively, in comparison with the reference. Finale the failure mode for reference beam was flexural failure type (plastic hinge), while, the failure mode for strengthened beams by CFRP without and with end anchorage plates was sudden; because of the de-bonding at the end of the CFRP strips and at the end of carbon fibre that due to the stress concentration at the ends of the CFRP.